Easy Audios: from Readability to Listenability - Machuca Ayuso, María J.; Matamala, Anna (Journal of Audiovisual Translation, 2025)
This article provides a foundational exploration of key concepts related to the development of “easy audios”, an emerging accessibility service based on Easy Language (EL). EL encompasses a set of guidelines for simplifying language to enhance accessibility for individuals with reading comprehension difficulties, applicable across various formats, including written, oral, and multimodal content. The article examines the transition from easy written texts to easy audios, focusing on readability and listenability, crucial concepts in both foreign language learning and audiovisual accessibility. The study highlights existing practices in easy subtitles and audio descriptions and discusses innovative hybrid services such as easy audios, which combine EL and audiovisual translation principles. Furthermore, the research explores how easy audios could be developed for improved comprehension, particularly for those who struggle with audiovisual content. Conclusions suggest that essential features for listenability in easy audios have been identified, highlighting the importance of clear linguistic structures, appropriate sound mixing, and careful prosody. However, the article emphasises the need for further research to fully understand and refine these features, particularly as they relate to the development of easy audio services in various contexts. Lay summary Easy Language aims to make texts easier to understand. There are recommendations and some research on written Easy Language, but not so much on spoken Easy Language. The WEL project aims to investigate spoken Easy Language, more specifically the so-called “easy audios”. At the beginning of the WEL project, we revised existing publications to better understand some key concepts. This is what we are presenting in this article. In this article, we define some key notions: when we refer to written texts, we talk about legibility and readability. When we refer to spoken words, we talk about intelligibility and listenability. In this article, we look at the concept of listenability in foreign language learning and audiovisual accessibility to see what other researchers have found. We also provide a summary of what current guidelines recommend. At the end of the article, we summarise some key features that improve listenability and focus on prosodic elements. These include: a) clear enunciation with a focus on pronunciation; b) appropriate prosody, in terms of: pitch, volume, voice quality, speech rate, and pauses. Conclusions indicate that important features for making audios easy to listen include clear language, proper sound mixing, and careful rhythm. However, the article stresses that more research is needed to better understand and improve these features, especially when creating easy audio services for different situations.